Willingness-to-pay for urban green space: A meta-analysis of surveys across China - Wikurendra, Edza A.; Aulia, Aulia; Fauzi, Muhammad L.; Fahmi, Iqbal; Amri, Ikhwan (Narra X, 2023)
Sustainable ecosystem services are increasingly recognized amid rapid regional transformation. While the rate of urbanization in China continues to rise, there is an urgent need to evaluate public preferences and their associated economic values concerning urban green space (UGS). The aim of this study was to calculate the overall willingness-to-pay (WTP) for UGS across China. Literature search was performed systematically on Scopus, Scilit, PubMed, and Google Scholar databases on 11 November 2023. Studies reporting the WTP in China were included in the analysis. Quality of the included studies were appraised by using Q-SSP tool consisting of 20-item quality of survey studies in psychology. To calculate the overall willing to pay rate and WTP, a meta-analysis was performed using restricted maximum-likelihood model on raw proportions. A total of nine studies were included comprised of 9381 valid responses with high quality according to Q-SSP (score: 70–90%). Findings from the meta-analysis indicated that the rate of willing to pay for UGS was 70.8% (95%CI: 60%, 82%; p-Het<0.001, I2= 99.37%). The rate was not affected by sample size, age, gender, and education (p>0.05). Among mainland Chinese population alone, the average minimum WTP was 2.97 USD/month, and increased to 3.36 USD/month if combined with Hong Kong population. A majority of over 70% Chinese population were willing to pay for UGS. Nevertheless, high heterogeneity in the pooled estimates suggest the importance of addressing contextual variables and presence of regional disparities.